Influence of Interactive Media-based Kahoots Application with Islamic Questions on Students’ Learning Outcomes - Faiq Alwan Fauzan; Ishaq Nuriadin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Learning mathematics has a significant role in forming the students’ attitudes and mindsets and solving problems independently. The problems students face have low mathematics learning outcomes and feel that the material they are learning is complex and the way of learning mathematics is less effective. The teacher is still the center of mathematics's learning process. Therefore, this study aims to determine the effect of Kahoot learning media on the mathematics learning outcomes of fifth-grade students at MI Unwanul Huda. The Kahoot media application is interactive and exciting, so students do not feel bored and bored in learning. This application is a game in the form of a test. The method used is a quantitative experimental method in the form of a quasi-experimental design with one group pre-test and post-test design. The saturated technique sampling consisted of class V, with 28 students. The data collection technique used is the test. The results of the hypothesis test used the t-test with parametric statistics. It is known that the average post-test of student learning outcomes using Kahoot learning media is 65.00, and the average pre-test of student learning outcomes is 37.14. So it can be concluded that there is an influence on the mathematics learning outcomes of students who use Kahoot learning media.